Transmission range and density gradient management to avoid bottleneck around base station in wireless sensor network. (2nd December 2009) - Padmanabh, Kumar; Roy, Rajarshi
Base station is a special node in a sensor network. It connects an individual sensor node to the outside world. Mostly base stations have sufficient battery power. However, the nodes which are in the proximity of base station have limited battery power. The information generated by other nodes gets shipped to the base station via the nodes which are adjacent to the same. Thus in addition to the information generated by them, the nodes around the base station also have to forward the data of other nodes to the base station. In this way these nodes will have to bear more communication responsibilities than peripheral nodes. The batteries of these nodes get exhausted rapidly and thus they create a bottleneck for prolonged communication. In this paper, we propose to optimise the topology by optimising the transmission power and introducing redundancy in the system in different topological scenarios to avoid this bottleneck phenomenon. The analytical and experimental results demonstrate that using our proposed algorithm all nodes will exhaust its battery at almost the same moment of time. There will no more be a bottleneck in prolonged communication.